Between the old and the new : the impact of communal traditional values and practices on the cultural identity of young and old Basotho - Beiroth, Ann Christin (2017)
Lesotho, in Southern Africa, has long been neglected in communication research. To address this void, the present study investigates what traditional values and traditional rituals exist in today’s Lesotho, how important these are respectively to the young and old generation of Basotho, and how traditional values and practices help the formation of cultural identities of old and young people of Lesotho. The theory behind this study was cultural identity theory by Collier and Thomas (1988), a theory which had mostly been used in the context of ethnic minority research. To expand the use of this theory, through 18 qualitative interviews of both older and younger Basotho, this study found respect, sharing, and gender roles to be the prevalent values. Funeral rituals, marriage customs, and ancestor rites were also important. Through thematic analysis, this study found differences between the old and the young generation in the perception of importance of most traditions, indicating an age-related cultural identity. At the same time, most participants avowed a national cultural identity, which used traditions to stress cohesion. This study shows how fluid cultural identities can be, and, thanks to its novel context, it presents a valuable addition to cultural identity research. Because of the non-generalizability of this study, the results will need to be confirmed by future research.